2007
DOI: 10.1172/jci30489
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Gi and Gq/Gs pathways in airway smooth muscle regulates bronchial contractility and relaxation

Abstract: Receptor-mediated airway smooth muscle (ASM) contraction via G αq , and relaxation via G αs , underlie the bronchospastic features of asthma and its treatment. Asthma models show increased ASM G αi expression, considered the basis for the proasthmatic phenotypes of enhanced bronchial hyperreactivity to contraction mediated by M 3 -muscarinic receptors and diminished relaxation mediated by β 2 -adrenergic receptors (β 2 ARs). A causal effect between G i expression and phenotype has not been established, nor hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 27 publications
2
59
1
Order By: Relevance
“…More recently, Liggett and co-workers (38) provided evidence supporting a direct causal relationship between changes in G i expression and altered airway responsiveness by demonstrating that transgenic mice that overexpress the G␣i2-subunit in ASM exhibit decreased ␤2AR-mediated airway relaxation, whereas ␤2AR function is increased in mice expressing a G␣i2 inhibitory peptide in ASM. Unexpectedly, these authors also reported that wild-type mice pretreated with PTX exhibited increased airway constrictor responses to methacholine, as did mice expressing the G␣i2 inhibitory peptide, whereas the bronchoconstrictor responses were decreased in mice overexpressing G␣i2 in ASM (38). The latter findings appear contradictory to those of the present study, as we found that pretreatment with PTX inhibited the heightened ASM constrictor responses to ACh accompanying heterologous ␤2AR desensitization while having no effect on ASM contractility under control conditions (Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…More recently, Liggett and co-workers (38) provided evidence supporting a direct causal relationship between changes in G i expression and altered airway responsiveness by demonstrating that transgenic mice that overexpress the G␣i2-subunit in ASM exhibit decreased ␤2AR-mediated airway relaxation, whereas ␤2AR function is increased in mice expressing a G␣i2 inhibitory peptide in ASM. Unexpectedly, these authors also reported that wild-type mice pretreated with PTX exhibited increased airway constrictor responses to methacholine, as did mice expressing the G␣i2 inhibitory peptide, whereas the bronchoconstrictor responses were decreased in mice overexpressing G␣i2 in ASM (38). The latter findings appear contradictory to those of the present study, as we found that pretreatment with PTX inhibited the heightened ASM constrictor responses to ACh accompanying heterologous ␤2AR desensitization while having no effect on ASM contractility under control conditions (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, in this context, recent studies have demonstrated that the acute cAMP responses detected in subcellular microdomains of HEK293 cells exposed to a ␤2AR or prostanoid receptor (EP2 and EP4) agonist are rapidly attenuated by PKA-dependent PDE4 activity (notably involving PDE4D5), which also mediates acute homologous desensitization of these receptors to subsequent agonist administration, as well as acute heterologous desensitization of the ␤2AR following exposure to an EP2/EP4 agonist (48,49). Of significance, this rapid PKA-dependent/PDE4D-mediated attenuation of cAMP signaling and desensitization to ␤2AR and EP2/EP4 agonists was not detected in the presence of receptor-independent activation of adenylyl cyclase in forskolin-exposed HEK293 cells (38). Recent evidence supports the notion that PDE4D5 represents the key regulator of acute ␤2AR-stimulated cAMP signaling in human ASM cells (5).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Increases in PGE 2 levels within the lung have been implicated in the initiation and/or exacerbation of AHR (19,20). To determine the effect of moderate-intensity aerobic exercise on PGE 2 levels within the lungs of OVA-treated mice, mice were subjected to bronchoalveolar lavage and the resulting BALF was analyzed for changes in PGE 2 content.…”
Section: Moderate-intensity Aerobic Exercise Attenuated Pge 2 Levels mentioning
confidence: 99%
“…There appears to be a differentiation between downregulation of the β2AR (causing less effective bronchodilatation) and enhanced contractile signaling (causing enhanced AHR) due to chronic activation of the β2AR. 37 Both occur with regular use of beta2-agonists.…”
Section: (Ref)mentioning
confidence: 99%